Development of Augmented Reality-based Learning Media to Improve Students' Understanding of Moral Affairs Lessons in Class IX MTs - Hasanah, Uswatun; Asri, widiatsih; Eges Tri, Wahyuni (Journal of Education Technology and Inovation, 2024)
The product developed in this media is an Augmented Reality-based learning medium that is an application. Basically, Augmented Reality media is a software to create 3D image, video, text and audio devices into a program created.The study aims to determine the effectiveness and level of students' understanding of the material of faith to the last days using the Augmented Reality media. Research and development techniques, or simply "research and development," are employed in this kind of study. The development product validated by the media expert receives a 79% rating with a valid category, while the media validation receives a 97.5% rating with the highly valid category used. Samples from class IX students are then used, using one group pretest and posttest design patterns. Dick and Carey's nine-stage development design model is used. The daily repeat values before and after the therapy were the data, which were then subjected to t test analysis. The study's findings demonstrated the high degree of efficacy and comprehension of the augmented reality-based learning resources employed, particularly in the academic areas